2020
DOI: 10.2174/1573409915666191025114009
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Peptidyl-prolyl Cis-trans Isomerase NIMA-interacting 1: A Structure-based Virtual Screening Approach to Find Novel Inhibitors

Abstract: Background : Peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (Pin1) is an enzyme that isomerizes phosphorylated serine or threonine motifs adjacent to proline residues. Pin1 has important roles in several cellular signaling pathways, consequently impacting the development of multiple types of cancers. Methods: Based on the previously reported inhibitory activity of pentacyclic triterpenoids isolated from the gum resin of Boswellia genus against Pin1, we designed a computational experiment using molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Different studies have reported that KA derivatives act as inhibitors of tyrosinase [ 19 , 21 , 22 , 23 ]. Initially, we investigated the selectivity of fourteen KA derivatives against the tyrosinase binding pocket using molecular docking, a computational tool widely applied in structure-based virtual screening approaches [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. First, re-docking simulations using the crystallographic structure of KA were performed in the CSD Gold [ 33 ] program to validate our docking protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have reported that KA derivatives act as inhibitors of tyrosinase [ 19 , 21 , 22 , 23 ]. Initially, we investigated the selectivity of fourteen KA derivatives against the tyrosinase binding pocket using molecular docking, a computational tool widely applied in structure-based virtual screening approaches [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. First, re-docking simulations using the crystallographic structure of KA were performed in the CSD Gold [ 33 ] program to validate our docking protocol.…”
Section: Resultsmentioning
confidence: 99%
“…With the increased interest in developing new mosquito repellents from natural products (NPs), essential oils are considered an interesting source due to their widely diverse class of volatile and low-molecular-weight compounds and also to their ovicidal, larvicidal, and repellent activities against human disease vectors. 2226 With the resurgence of NPs in the development of new bioactive compounds by the pharmaceutical and cosmetic industries 2730 and due to the cutting-edge technologies of combinatory chemistry, cheminformatics, and molecular modeling, new studies have focused on essential oils to explore their potentiality as mosquito repellents. 23,31,32 Recently, we have used different computational approaches to investigate biomolecular systems with emphasis on enzymatic reaction and inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…With the increased interest in developing new mosquito repellents from natural products (NPs), essential oils are considered an interesting source due to their widely diverse class of volatile and low-molecular-weight compounds and also to their ovicidal, larvicidal, and repellent activities against human disease vectors. With the resurgence of NPs in the development of new bioactive compounds by the pharmaceutical and cosmetic industries and due to the cutting-edge technologies of combinatory chemistry, cheminformatics, and molecular modeling, new studies have focused on essential oils to explore their potentiality as mosquito repellents. ,, Recently, we have used different computational approaches to investigate biomolecular systems with emphasis on enzymatic reaction and inhibition. In the present study, using an in silico approach, we performed a comprehensive analysis of the potentiality of 1633 compounds from the essential oils of 71 botanical families deposited in the Essential Oil Database (EssOilDB) by combining a structure- and ligand-based virtual screening, using as reference the structure of DEET complexed to the OBP1 homodimer of A. gambiae ( Agam OBP1).…”
Section: Introductionmentioning
confidence: 99%
“…Pin1 is aberrantly activated in diverse malignant tumors and has emerged as an attractive therapeutic target. da Costa et al used various computational approaches such as molecular docking, pharmacophore filtering, and structural clustering allied to molecular dynamics simulations and binding free energy calculations to show that nimbolide interacts with high affinity with the Pin1 substrate peptide and destabilizes Pin1 structure.…”
Section: Nimbolide Abrogates Oncogenic Signalingmentioning
confidence: 99%